Properdin Pattern Recognition on Proximal Tubular Cells Is Heparan Sulfate/Syndecan-1 but Not C3b Dependent and Can Be Blocked by Tick Protein Salp20 - Lammerts, Rosa G. M.; Talsma, Ditmer T.; Dam, Wendy A.; Daha, Mohamed R.; Seelen, Marc A. J.; Berger, Stefan P.; van den Born, Jacob (Frontiers in Immunology, 2020)
Introduction – Proteinuria contributes to progression of renal damage, partly by complement activation on proximal tubular epithelial cells. By pattern recognition, properdin has shown to bind to heparan sulfate proteoglycans on tubular epithelium and can initiate the alternative complement pathway (AP). Properdin however, also binds to C3b(Bb) and properdin binding to tubular cells might be influenced by the presence of C3b(Bb) on tubular cells and/or by variability in properdin proteins in vitro. In this study we carefully evaluated the specificity of the properdin – heparan sulfate interaction and whether this interaction could be exploited in order to block alternative complement activation. Methods – Binding of various properdin preparations to proximal tubular epithelial cells (PTEC) and subsequent AP activation was determined in the presence or absence of C3 inhibitor Compstatin and properdin inhibitor Salp20. Heparan sulfate proteoglycan dependency of the pattern recognition of properdin was evaluated on PTEC knocked down for syndecan-1 by shRNA technology. Solid phase binding assays were used to evaluate the effectivity of heparin(oids) and recombinant Salp20 to block the pattern recognition of properdin. Results – Binding of serum-derived and recombinant properdin preparations to PTECs could be dose-dependently inhibited (P<0.01) and competed off (P<0.01) by recombinant Salp20 (IC50: ~125 ng/ml) but not by Compstatin. Subsequent properdin-mediated AP activation on PTECs could be inhibited by Compstatin (P<0.01) and blocked by recombinant Salp20 (P<0.05) . Syndecan-1 deficiency in PTECs resulted in a ~75% reduction of properdin binding (P=0.057). In solid-phase binding assays, properdin binding to C3b could be dose-dependently inhibited by recombinant Salp20> heparin(oid) > C3b. Discussion – In this study we showed that all properdin preparations recognize heparan sulfate/syndecan-1 on PTECs with and without Compstatin C3 blocking conditions. In contrast to Compstatin, recombinant Salp20 prevents heparan sulfate pattern recognition by properdin on PTECs. Both complement inhibitors prevented properdin-mediated C3 activation. Binding of properdin to C3b could also be blocked by heparin(oids) and recombinant Salp20. This work indicates that properdin serves as a docking station for AP activation on PTECs and a Salp20 analogue or heparinoids may be viable inhibitors in properdin mediated AP activation.